PARENTAL INVOLVEMENT IN THE EDUCATION OF CHILDREN IN PUBLIC LOWER PRIMARY SCHOOLS IN NYANDARUA WEST SUB-COUNTY, NYANDARUA COUNTY, KENYA - Kiboi, Alice; Mariene, Dr. John; Mwaki, Paul (IJRDO- Journal of Educational Research, 2017)
The purpose of this research was to establish the extent to which parents are involved in the education of children in public lower primary schools in Nyandarua West Sub-County. The study was guided by four objectives; to establish the indicators of parental involvement in the children’s education in public lower primary schools, to examine how communication influences children education in public lower primary schools, to determine how home environment influences children’s education in public lower primary schools and to investigate parental provision of teaching and learning resources in the education of their children. The study revealed that there was parental involvement in the education of children in lower primary public schools through communication with teachers, especially during meetings on children’s performance, and regular follow-up. However, some parents had a negative attitude towards the education of their children and were involved to a limited extent in supporting their children with homework.